DESIGN OF PARAMETERS OPTIMIZATION FOR AUTOMOBILE SUSPENSION BASED ON ARTIFICIAL BEE COLONY ALGORITHM - ZHANG HaiTao; WANG AiGuo (Jixie qiangdu)
In view of defect of selecting parameters for automotive suspension system,optimizing method of determining the parameters based on local elitist strategy（ LES） and artificial bee colony algorithm（ ABC） was proposed through integrating great local seeking ability of LES and great global seeking ability of ABC algorithm.Through Matlab/Simulink software,The simulation of suspension system were carried out; in which integral white noise model were the road input. The simulation discovered that LES-ABC algorithm optimization algorithm has certain advantage compared with traditional algorithms and artificial bee colony algorithm. Riding comfort and handling performance could be enhanced through optimizing system parameters of automotive suspension.